3D printing stiff antibacterial hydrogels for meniscus replacement. (September 2021) - Yang, Rong; Fan, Chuanchuan; Dou, Yiming; Zhang, Xiaoping; Xu, Ziyang; Zhang, Qian; Sun, Yage; Yang, Qiang; Liu, Wenguang
Highlights: Gelatin enables printability of multiple H -bonding monomer (HM) into meniscus scaffold. Post-polymerization of HM and leaching out gelatin result in highly stiff hydrogels. The printed stiff hydrogel does not exhibit noticeable wear to cartilage in simulation test. ZIP-8 coating affords an antibacterial activity of the stiff hydrogel. Abstract: 3D printing of high-strength and stiff hydrogel is of great significance in customizing individualized load-bearing soft tissues, but faces a significant challenge. Herein, inspired by fugitive ink generally adopted in supporting bath printing, gelatin is employed as a sacrificial rheological modifier material to thicken the multiple hydrogen bonding monomer N -acryloylsemicarbazide (NASC), affording direct printability. Post-UV light irradiation-initiated polymerization of NASC results in robust hydrogel in spite of disturbance of hydrogen bonding caused by gelatin. Notably, PNASC H -bonding interactions is well reconstructed after high temperature dialyzing of gelatin, which resumes the tensile strength, Young's modulus, compressive modulus, of the printed hydrogels to 2.3 MPa, 26.25 MPa, 4.22 MPa, respectively. The NASC/gelatin can be printed into different architectures including meniscus, and the printed hydrogel does not exhibit noticeable wear to cartilage in simulation test of femoral wear. In addition, polydopamine coated-ZIF-8 is modified onto the surface of PNASC/gelatin hydrogels through one-pot synthesis method, thereby affording an antibacterial property without varying mechanical performance and wear property. This printed PNASC/gelatin scaffold with high strength, stiffness, better biocompatibility, low wear property, and built-in antibacterial activity hold potential as a meniscus substitute with a potent ability to minimize infection-induced implantation failure. Graphical abstract: Direct printing of multiple H-bonding monomer with an assistance of gelatin rheological modifier results in high strength and stiff hydrogel after post-polymerization of monomer and leaching out the thickener due to re-establishment of H-bonding interaction. This printed high-strength hydrogel has a low wear property, and anchoring of ZIF-8@PDA affords an antibacterial activity, portending a promising application toward meniscus replacement. Image, graphical abstract